Question

Solve: (x^4 – xy^3)dy + (2y^4 – x^3y)dx = 0

Answer #1

Solve the Differential Equation:
(2y^4 + xy)dx - (6x^2) dy= 0

Solve the following:
(3x^2 - y^2)dx + (xy - x^3y^-1)dy = 0

solve (x^2+2y^2)dx/dy = xy

Solve the equation.
(2x^3+xy)dx+(x^3y^3-x^2)dy=0
give answer in form F(x,y)=c

Solve the following system of differential equations:
dx/dt =x+2y
dy/dt =−x+3y

Solve the initial value problems.
1) x (dy/dx)+ 2y = −sinx/x , y(π) = 0.
2) 3y”−y=0 , y(0)=0,y’(0)=1.Use the power series method
for this one . And then solve it using the characteristic
method
Note that 3y” refers to it being second order
differential and y’ first

(x^2-4)dy/dx+xy-x^3+4x=0. y(3)=7

solve the differential equation
(2y^2+2y+4x^2)dx+(2xy+x)dy=0

Use the method for solving homogeneous equations to solve the
following differential equation.
(9x^2-y^2)dx+(xy-x^3y^-1)dy=0
solution is F(x,y)=C, Where C= ?

solve the bernqoulli equation dy/dx+xy+xy^2=0

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 5 minutes ago

asked 17 minutes ago

asked 21 minutes ago

asked 29 minutes ago

asked 37 minutes ago

asked 38 minutes ago

asked 44 minutes ago

asked 44 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago